PENGARUH LEMBAGA KEUANGAN MIKRO TERHADAP PENGEMBANGAN UMKM (Studi Pada Pinjaman Koperasi di Kabupaten Mojokerto, Jawa Timur) - Arini, Silvia Nurfita; Nurul Badriyah (Contemporary Studies in Economic, Finance and Banking, 2024)
This research aims to find out how microfinance institutions, especially cooperatives, influence the development of MSMEs with variables, namely the amount of financing and cooperative interest rates, influencing the development of MSMEs from the perspective of business profits. This research uses quantitative research methods with multiple linear regression analysis tools. The data used in this research is primary data obtained using questionnaires from respondents, namely 55 MSMEs in Mojokerto Regency. In this research, research results found that the variables of the amount of financing and interest rates set by cooperatives had an effect on the development of MSMEs (in terms of increasing turnover). From the results of this research, it is recommended that MSME players make more use of cooperatives as a place to obtain financing with the aim of developing MSMEs. And MSME players must be more able to distribute their business funds so that capital problems do not become an obstacle in developing their business.